Osmanlı bürokrasisinde Şâkirdlik: 18. yüzyılda başmuhasebe kalemi örneği - ÇETİN, ENGİN (My University, 2023)
In th Ottoman bureaucracy, individuals who were employed as kâtib (clerk) candidates were referred to as ‘shakird’ (apprentice). Initially, they were placed under the supervision of a narrow cadre of clerks within the Divan-ı Hümayun (Imperial Council). Over time, they began to work in key bureaucratic institutions such as the Bâbıâlî (Sublime Porte), Defterhâne (Storehouse of Ottoman Cadastral and Other Property Records), and Bâb-ı Defterî (Ottoman Institution for Financial Affairs), which became central pillars of the Ottoman bureaucracy from the mid-17th century onward. This group primarily consisted of young individuals and served as the primary resource for the Ottoman bureaucracy. While they shared some common characteristics, there were significant differences in the attributes, career trajectories, and job roles of shakirds required by various institutions. Within the already limited number of studies on the history of Ottoman institutions, there has been a noticeable gap in the literature concerning the shakirds, as researchers have primarily focused on the upper echelons of the empire’s bureaucracy.This paper aims to address this deficiency by discussing the nature of shakirds within the Ottoman bureaucracy. Given the impracticality of conducting comprehensive research on the entire bureaucracy, this study will use the Başmuhasebe Kalemi (Chief Accounting Office) in the 18th century as a case study. It will shed light on the recruitment patterns of the shakirds in the Başmuhasebe Kalemi, their numbers, working conditions, salaries and career paths.
Keywords: Sosyal ve Beşeri Bilimler; Tarih; Yeniçağ Tarihi; Social Sciences and Humanities; History; Modern History; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; TARİH; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; HISTORY; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; şâkird; kâtip; Başmuhasebe Kalemi; bürokrasi; 18. yüzyıl